2016
DOI: 10.1002/acp.3269
|View full text |Cite
|
Sign up to set email alerts
|

It Is Just Harder to Construct Memories for False Autobiographical Events

Abstract: SummaryBrewin and Andrews (2016) review studies using three research paradigms—imagination inflation, false feedback, and memory implantation—and the prevalence rate for false memories differs widely across paradigms. Vast differences also result depending on the scheme used to code the recall data. Framing memory as a constructive process reveals many of the similarities between cognitive processes involved in memory for true and false events, similarities that account for why memories are far less likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Empirical studies of these evocative effects have resulted in a complicated pattern of findings, with reports of both benefits and costs on recollection accuracy. Recent reviews have summarized these effects and highlighted contributing factors (e.g., Pezdek & Blandon-Gitlin, 2017;Scoboria et al, 2017;Storm & Soares, in press). However, the review offered in the current article casts the complicated pattern of findings in new light by calling attention to the striking ways in which the acts of looking at photographs vary considerably across prior studies.…”
Section: Purpose and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies of these evocative effects have resulted in a complicated pattern of findings, with reports of both benefits and costs on recollection accuracy. Recent reviews have summarized these effects and highlighted contributing factors (e.g., Pezdek & Blandon-Gitlin, 2017;Scoboria et al, 2017;Storm & Soares, in press). However, the review offered in the current article casts the complicated pattern of findings in new light by calling attention to the striking ways in which the acts of looking at photographs vary considerably across prior studies.…”
Section: Purpose and Overviewmentioning
confidence: 99%
“…Thus far, studies of the costs associated with looking at photographs have focused on recollections of actual experiences from one's personal past. However, potential costs that have garnered considerable attention from memory researchers focus on photographs associated with fictional events (e.g., Garry & Wade, 2005;Pezdek & Blandon-Gitlin, 2017;Scoboria et al, 2017;Strange et al, 2006Strange et al, , 2008. As part of what memory researchers refer to as implantation procedures, participants are asked to try to recall several childhood events, rating the likelihood they experienced these events as children.…”
Section: Costs Of (Re)viewing Photographs On Memorymentioning
confidence: 99%
“…Research in false memory has found that the plausibility of an event, that is, the likelihood of the event’s occurrence (Pezdek, Blandon-Gitlin, Lam, Hart, & Schooler, 2006; Pezdek, Finger, & Hodge, 1997) is an important moderator to the generation of false memories. Thus, individuals are less likely to incorporate misinformation into their memories of an event when that information describes an event that is implausible (unlikely to have occurred; Mazzoni, Loftus, & Kirsch, 2001; Pezdek & Blandon-Gitlin, 2017; Pezdek et al, 1997), because they are presumably more likely to correctly attribute the information to its source, rather than misattributing it to their personal experience (Johnson, 2006; Johnson et al, 1993; Johnson & Raye, 1981, 2000; Mitchell & Johnson, 2000, 2009). For example, research has shown that events that were more consistent with individuals’ script-level knowledge (i.e., memory traces for similar, related experiences) and, thus more likely to have occurred in the past (e.g., increased plausibility of the false memory) were more likely to result in memory errors.…”
Section: Prior Literaturementioning
confidence: 99%